The Effect of Academic Self-Efficacy and School Climate on Academic Achievement in Mathematics with Achievement Motivation as Mediator - Siti Khosiyah (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Aim: This study aims to determine the effect of academic self-efficacy and school climate on mathematics academic achievement with achievement motivation as a mediator. The population of this research is all students at SMK Sasmita Jaya, Pamulang. The sample of this research was 410 people, and the sample was taken using a probability sampling technique with simple random sampling. Researchers used student report cards as a measure of academic achievement in mathematics according to Winkel's theory (2007), academic self-efficacy used as a measure developed by Sagone and Caroli (2014), school climate used as a measure developed by Gage et al. (2015), achievement motivation uses a measuring tool developed by McClelland (1987). Analysis of the data used in this study with the statistical technique of structural equation modeling using AMOS and to test the validity of the constructs using LISREL 8.7. Results: achievement motivation does not directly affect academic achievement in mathematics; it can be seen from the t count -454. Academic self-efficacy significantly affects mathematics achievement because the value of t arithmetic is 6,411. School climate significantly influences mathematics academic achievement with a t value of 3.234. Conclusion: The research data were analyzed using the statistical structural equation modeling technique. It concluded that there was a significant effect between academic self-efficacy and school climate on mathematics academic achievement. The results of the structural model test with achievement motivation as a mediator variable indicate that achievement motivation has an insignificant effect in moderating the effect of academic self-efficacy and school climate on mathematics academic achievement.